The Stele of YHWH in Egypt the Prophecies of Isaiah 18-20 concerning Egypt and Kush. - Balogh, Csaba (Leiden : BRILL, 2011)
This book provides a thorough analysis of Isaiah 18-20, concerned with Egypt and Kush, from the earliest stages to their final contextualisation within the developing corpus of the Isaianic prophecies regarding the nations.
Preface; Abbreviations; Chapter One Introduction; Chapter Two Collections of Foreign Nation Prophecies as Context for Isaiah 13-23; Chapter Three Reconstructing the Broken Stele of Yhwh: The Foreign Nation Prophecies of Isaiah 13-23 as Context for Isaiah 18-20; Chapter Four Lands of Riddles: The Analysis of Isaiah 18; Chapter Five From Chaos to Covenant: The Analysis of Isaiah 19; Chapter Six Naked Truth: The Analysis of Isaiah 20; Chapter Seven Conclusion; Bibliography; Index of Authors; Index of Biblical References; Index of Non-Biblical References.
Description based on print version record.
Keywords: Bible. O.T. Isaiah -- Prophecies -- Egypt; Bible. O.T. Isaiah XVIII-XX -- Criticism, interpretation, etc; Bible. O.T. Isaiah -- Prophecies -- Cushites; Bible. O.T. Isaiah -- Prophecies -- Ethiopia; Cushites -- Prophecies; Egypt in the Bible; Ethiopia in the Bible; Religion; Bible. -- Prophecies -- Egypt; Bible. -- Prophecies -- Ethiopia; Bible. -- Prophecies -- Cushites; Egypt in the Bible; Ethiopia in the Bible; Cushites -- Prophecies; RELIGION / Biblical Studies / Prophets; Electronic books